ANALISIS URGENSI SISTEM MANAJEMEN TALENTA GURU DI UPTD SD NEGERI 074056 DAHANA HUMENE KECAMATAN GUNUNGSITOLI IDANOI KOTA GUNUNGSITOLI - Gea, Rika Permata; Ndraha, Ayler Beniah; Hulu, Fatolosa; Waruwu, Sukaaro (FEB Universitas Sam Ratulangi Manado, 2023)
In today's globalization, it is inevitable that school organizations need to prepare human resources (HR) in order to adapt and improve school performance to be able to compete on a global scale. One of the efforts is to improve teacher performance. So that talent management is a concept that starts from how to plan, get, develop and maintain a talent in an organization or company. Because talent management is very important, therefore talent management is also needed in the world of education, which focuses on the professionalism of a teacher. This research was conducted in a type of qualitative research with a descriptive approach because this type of research has the aim of describing and analyzing phenomena, events, or social activities that occur. The teacher talent management system at UPTD SD Negeri 074056 Dahana Humene has several shortcomings and challenges that need to be overcome. First, the honorary teacher selection process has not been effective and optimal, which affects school quality and standards. Secondly, the placement of honorary teachers often does not match their expertise or academic qualifications, which can impact on the quality of teaching and learning. Thirdly, the development and training provided by schools do not always match teachers' needs and expertise, especially in terms of using IT and making technology-based learning tools. For this reason, schools need to make some improvements. In the selection process, schools should implement effective procedures, develop clear and relevant selection criteria, and conduct regular evaluation and improvement. In terms of training and development, schools should better understand teachers' skills and knowledge needs, design appropriate training programs and ensure the training and development process is sustainable. In addition, schools should also ensure that the placement of honorary teachers is in line with their expertise and academic qualifications.